Evolution of Oxygen Ligands upon Large Redox Swings of Li3IrO4. Issue 6 (23rd June 2021) - Li, Haifeng; Perez, Arnaud J.; Taudul, Beata; Boyko, Teak D.; Freeland, John W.; Doublet, Marie-Liesse; Tarascon, Jean-Marie; Cabana, Jordi
Abstract : The limits of intercalation electrochemistry continue to be tested in the quest for ever increasing gains in the storage capability of Li-ion cathodes. The subsequent push for multi-electron reactivity has led to the recognition of the extremely versatile role of oxide ligands in charge compensation when there is a large redox swing. Li3 IrO4 is a unique model of such activity because it can reversibly cycle between Li1 IrO4 and Li4.7 IrO4 . Here, X-ray spectroscopy, magnetic measurements and computational simulations uncover the evolution of O states in the different steps, compared to the involvement of Ir. While the process between Li1 IrO4 and Li3 IrO4 is dominated by the unconventional lattice oxygen redox, the process between Li3 IrO4 and Li4.7 IrO4 involves a conventional change of the formal oxidation state of Ir, which affects O due to the high covalency. The O states of Li3 IrO4 exhibit a very high reversibility after the whole 3.7-electron process, completely restoring the pristine state.